Cardio-embolic stroke following remote blunt chest trauma - Arora, Sonali (2013)
A cardio-embolic stroke as a sequela of remote blunt chest trauma is a rare clinical presentation. Blunt chest trauma can cause various acute cardiac complications like arrhythmias, cardiac contusion etc. However, delayed consequences such as left ventricular thrombus resulting in thromboembolic phenomena are reported infrequently. A 30-year-old healthy man presented to an outside facility with transient neurological deficits. An MRI brain showed lesions suggestive of embolic etiology. A trans-thoracic echocardiogram (TTE) showed a 1.5 × 1.5 cm mass present in the left ventricular (LV) apex. Patient was transferred to our institution for cardiac surgery evaluation. On detailed questioning, he reported an incident of blunt chest trauma during a martial arts exhibition fight that took place 2 years back. Given this history, a cardiac catheterization was done, which showed 30% stenosis in mid-left anterior descending artery (LAD) without any other significant obstructive lesion. A trans-esophageal echocardiogram (TEE) showed akinesis of the LV apex and confirmed TTE finding of a mass, consistent with an apical thrombus. Surgery was deferred and patient was started on anticoagulation. A cardiac MRI done 2 weeks later showed evidence of apical infarction in the LAD territory. LAD is the most commonly affected coronary vessel by blunt traumatic injuries, likely due to its vulnerable anatomical position on the anterior aspect of the heart. A variety of mechanisms including intimal tear, rupture and spasm have been implicated in the pathogenesis of myocardial infarction after blunt chest trauma.